Pengaruh pemberian tepung biji durian sebagai bahan pengisi bakso daging itik petelur afkir terhadap daya susut masak dan uji organoleptik - Abu Bakar; Permata Ika Hidayati; Tri Ida Wahyu Kustyorini (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2017)
ABSTRACT The purpose of this research is to know the effect of giving of durian seed meal as filling material of laying duck meatballs with organoleptic test and cooking shrinkage on elasticity, aroma, taste, color and texture. This method uses a complete Randomized design with four repetitions. Grain levels of durian 0% (P0), 5% (P1), 10% (P2), 15% (P3), and 20% (P4) durian grains. Using single variance analysis data. The results of organoleptic test and cooking shrink showed that in P0 and P1 treatment with 0-5% durian flour level there was a very real effect (P<0.01). While on P2, P3 and P4 does not influence good elasticity, aroma, taste, color, and texture. This is why more and more level of durian seed meal will decrease. Suggested in the process of making duck meatballs using 95% tapioca flour with 5% durian seed meal